Pregnant Mother's Anxiety Level On Stunting Risk - Hidayati, Eni; Damayanti, Sifana Ayu; Rahayu, Desi Ariyana; Mubin, Mohamad Fatkhul; Hidayati, Tri Nur (University of Muhammadiyah Semarang, 2022)
Pregnancy at a young age and over the age of 35 is vulnerable to causing pregnant women to experience various risks of pregnancy because pregnant women at a young age do not know much about how to maintain their pregnancy conditions and pregnant women over the age of 35 experience a decrease in nutrient absorption so they are easy to experience various kinds of problems. One of the risks of pregnancy is stunting. Pregnant women usually experience a psychological decline that causes anxiety in themselves. So that it also has an impact on the growth and development of the prospective baby. The type of research used is an analytical approach. The design of this study used a cross-sectional approach. The population in this study were pregnant women in the Sembungharjo village area with a total of 27 pregnant women using a total sampling of data analysis using the chi-square test. The results of the study from 27 respondents were obtained that pregnant women with mild anxiety among as many as 16 respondents (59.3%), moderate anxiety among as many as 5 respondents (18.5%), and no anxiety among as many as 6 respondents (22.2%). Respondents with severe anxiety were 0 (0%). A total of 27 pregnant women respondents found that as many as 5 respondents (18.5%) had low risk while 22 respondents (81.5%) were not at risk, and pregnant women with high risk were 0 (0%). The conclusion is that there is no relationship between the anxiety level of pregnant women and the risk of stunting in Sembung Harjo sub-district, Genuk sub-district with a p-value of 0.366 (a> 0.05).